Characterization of Eye Signals in The Noble Prophetic Hadith - Daad Younis Hussein Abdullah; Zulazhan Ab. Halim; Mohd Fauzi Abdul Hamid (USIM Press, 2024)
Vol. 26 No. 1 (2022): Journal of Islamic Social Sciences and Humanities